Understanding the new customer path in omni channel marketing strategy at berrybenka and its impact on better customer engagement through marketing 4.0 perspective - Suhartanto, Meikel; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2019)
Abstract - Berrybenka is an Indonesian brand of online shopping store that offers and curates fashion apparel (women and men), beauty products and accessories from various brand locally and internationally, include creating their own private independent label, which become their priority business today. Its step to open offline store as omnichannel strategy seems like conflicting with other brands as their competitor, in which they are only penetrating online channel. In this research the author focuses in analysing the new customer path of Berrybenka’s omnichannel marketing strategy through The Five A’s framework and provide improvement solutions for Berrybenka to have a better customer engagement. This research is using quantitative methodology to collect the data and analyze it from gathered information based on The Five A’s framework theory in Marketing 4.0 perspective and questionnaire data result. Based on generated data, the author then finds out solution for each customer path starting from phase of ‘Awar’e, the author gives initiative plan for increasing brand awareness, improvement for brand appeal in the phase of ‘Appeal’, solutions to increase brand attractiveness in the phase of ‘Ask’, and initiative plans to increase sales conversion in the phase of ‘Act’, also initiative plans to strengthen brand advocacy between customers in the phase of ‘Advocacy’. Therefore, in order to have better customer engagement, Berrybenka should understand how to manage all touchpoints across all integrated channels through The Five A’s framework. At the end, it should be followed by implementing all initiative plans in every phase of the new customer path.Keywords: new customer path, omnichannel marketing, touchpoints, channels, customer engagement